2020
DOI: 10.1080/01658107.2020.1821065
|View full text |Cite
|
Sign up to set email alerts
|

Late Onset Macular Oedema in a Patient with Multiple Sclerosis Treated with Fingolimod

Abstract: Macular oedema is a rare complication of fingolimod treatment. It usually presents within 3-4 months, but occasionally presents later. It can resolve without treatment despite continuation of fingolimod treatment. Herein we report a case of very late onset macular oedema in a 49-year-old woman with multiple sclerosis treated with fingolimod for 7 years. The patient presented with blurred vision in both eyes with visual acuities of 20/32 in her right eye and 20/25 in her left eye. She had macular oedema, that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…One case without risk factors occurred after 6 years of ozanimod exposure; delayed onset of ME is unusual but has been reported after 7 years of fingolimod use. 36,37 Bradycardia was infrequent, occurring mostly in those who switched from interferon β-1a or ozanimod 0.46 mg to ozanimod 0.92 mg. Similarly, bradycardia is uncommon after the first year of fingolimod use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One case without risk factors occurred after 6 years of ozanimod exposure; delayed onset of ME is unusual but has been reported after 7 years of fingolimod use. 36,37 Bradycardia was infrequent, occurring mostly in those who switched from interferon β-1a or ozanimod 0.46 mg to ozanimod 0.92 mg. Similarly, bradycardia is uncommon after the first year of fingolimod use.…”
Section: Discussionmentioning
confidence: 99%
“…One case without risk factors occurred after 6 years of ozanimod exposure; delayed onset of ME is unusual but has been reported after 7 years of fingolimod use. 36 , 37 …”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported fingolimod-associated ME post cataract surgery being resolved with STTA 6 and fingolimod-associated ME treated with intravitreal injection and continued fingolimod use 7 (as well as fingolimod discontinuation without topical eye-drop instillation 8 ), to the best of our knowledge, this is the first reported case of bilateral ME post cataract surgery that spontaneously resolved at 13-months postoperative following initial treatment with fingolimod at the current lower FDA-approved dose and continued fingolimod use.…”
Section: Discussionmentioning
confidence: 97%
“…The therapeutic effects of fingolimod on the brain are mostly mediated by S1P1 (sphingosine-1-phosphate receptor 1) receptors, which are highly expressed in astrocytes and comparatively less expressed in neurons, oligodendrocytes, and microglia ( Choi et al, 2011 ). The protective effect of fingolimod has been reported to be greater in astrocytes than in microglia ( Camós-Carreras et al, 2020 ). When astrocytes are activated, they become hypertrophied occupying more area ( Borges et al, 2003 , Shapiro et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%